#### Chemical Equations Balanced on 06/17/19

 Equations balanced on the previous day Equations balanced on the next day
 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 107 108 109 110 111 112 113 114 115 116 117 118 119 120 121 122 123 124 125 126 127 128 129 130 131 132 133 134 135 136 137 138 139 140 141 142 143 144 145 146 147 148 149 150 151 152 153 154 155 156 157 158 159 160 161 162 163 164 165 166 167 168 169 170 171 172 173 174 175 176 177 178 179 180 181 182 183 184 185 186 187 188 189 190 191 192 193 194 195 196 197 198 199 200 201 202 203 204 205 206 207 208 209 210 211 212 213 214 215 216 217 218 219 220 221 222 223 224 225 226 227 228 229 230 231 232 233 234 235 236 237 238 239 240 241 242 243 244 245 246 247 248 249 250 251 252 253 254 255 256 257 258 259 260 261 262 263 264 265 266 267 268 269 270 271
Co + Br2 = CoBr2 =>
Co + Br2 = CoBr2

Cl2 + LiBr = Li + ClBr =>
Cl2 + 2 LiBr = 2 Li + 2 ClBr

Pb3O4 + HCl = PbCl2 + H2O + Cl2 =>
Pb3O4 + 8 HCl = 3 PbCl2 + 4 H2O + Cl2

C2H2 + O2 = C + H2O =>
2 C2H2 + O2 = 4 C + 2 H2O

C10H18(l) + O2(g) = CO2(g) + H2O(l) =>
2 C10H18(l) + 29 O2(g) = 20 CO2(g) + 18 H2O(l)

FeSCN + NaOH = NaSCN + FeOH =>
FeSCN + NaOH = NaSCN + FeOH

C10H22 + O2 = CO2 + H2O =>
2 C10H22 + 31 O2 = 20 CO2 + 22 H2O

H2CO3 + KCl = K2CO3 + HCl =>
H2CO3 + 2 KCl = K2CO3 + 2 HCl

H2O + Cl2 = HCl + O2 =>
2 H2O + 2 Cl2 = 4 HCl + O2

C7H17 + O2 = CO2 + H2O =>
4 C7H17 + 45 O2 = 28 CO2 + 34 H2O

HBr + MG(OH)2 = MGBr2 + H2O =>
2 HBr + MG(OH)2 = MGBr2 + 2 H2O

C7H16 + O2 = CO2 + H2O =>
C7H16 + 11 O2 = 7 CO2 + 8 H2O

C2H6 + O2 = CO2 + H2O =>
2 C2H6 + 7 O2 = 4 CO2 + 6 H2O

NaHCO3 = Na2CO3 + H2O + CO2 =>
2 NaHCO3 = Na2CO3 + H2O + CO2

FeCl2 + Cl = FeCl3 =>
FeCl2 + Cl = FeCl3

ClO2 + H2O = HClO3 + HCl =>
6 ClO2 + 3 H2O = 5 HClO3 + HCl

Fe2O3 + C = Fe + CO =>
Fe2O3 + 3 C = 2 Fe + 3 CO

KMnO4 + HBr = MnBr2 + KBr + H2O + Br2 =>
2 KMnO4 + 16 HBr = 2 MnBr2 + 2 KBr + 8 H2O + 5 Br2

C7H6O2 + NaHCO3 = C7H5NaO3 + H2O + CO2 =>
14 C7H6O2 + 15 NaHCO3 = 15 C7H5NaO3 + 12 H2O + 8 CO2

C10H18(g) + O2(g) = CO2(g) + H2O(l) =>
2 C10H18(g) + 29 O2(g) = 20 CO2(g) + 18 H2O(l)

HNO3 + H2S = NO2 + H2O + S =>
2 HNO3 + H2S = 2 NO2 + 2 H2O + S

Ba(NO3)2 + NaOH = NaNO3 + Ba(OH)2 =>
Ba(NO3)2 + 2 NaOH = 2 NaNO3 + Ba(OH)2

H2S + O2 = H2O + SO2 =>
2 H2S + 3 O2 = 2 H2O + 2 SO2

C5H10 + O2 = CO2 + H2O =>
2 C5H10 + 15 O2 = 10 CO2 + 10 H2O

KNO3 = K2O + N2 + O2 =>
4 KNO3 = 2 K2O + 2 N2 + 5 O2

CH4O + O2 = CO2 + H2O =>
2 CH4O + 3 O2 = 2 CO2 + 4 H2O

C2H4 + H2 = C2H6 =>
C2H4 + H2 = C2H6

C3H8 + NH3 = HCN + H2 =>
C3H8 + 3 NH3 = 3 HCN + 7 H2

MgO + CO2 = MgCO3 =>
MgO + CO2 = MgCO3

P + HNO3 = NO2 + H2O + H3PO4 =>
P + 5 HNO3 = 5 NO2 + H2O + H3PO4

Ca + HCl = H2 + CaCl2 =>
Ca + 2 HCl = H2 + CaCl2

C6H12O + O2 = CO2 + H2O =>
2 C6H12O + 17 O2 = 12 CO2 + 12 H2O

C8H18 + O2 = CO2 + H2O =>
2 C8H18 + 25 O2 = 16 CO2 + 18 H2O

ZnCO3 = ZnO + CO2 =>
ZnCO3 = ZnO + CO2

Zn + HNO3 = Zn(NO3)2 + H2O + NO2 =>
Zn + 4 HNO3 = Zn(NO3)2 + 2 H2O + 2 NO2

AlCl3 + NaOH = Al(OH)3 + NaCl =>
AlCl3 + 3 NaOH = Al(OH)3 + 3 NaCl

C6H6O + O2 = CO2 + H2O =>
C6H6O + 7 O2 = 6 CO2 + 3 H2O

NaOH + H2SO4 = Na2SO4 + H2O =>
2 NaOH + H2SO4 = Na2SO4 + 2 H2O

CH4 + O2 = C02 + H2O =>
2 CH4 + 2 O2 = C02 + 4 H2O

C7H6O3 + NaHCO3 = C7H5NaO3 + H2O + CO2 =>
C7H6O3 + NaHCO3 = C7H5NaO3 + H2O + CO2

H2CO3 + Ca(OH)2 = CaCO3 + H2O =>
H2CO3 + Ca(OH)2 = CaCO3 + 2 H2O

K3PO4 + BaCl2 = KCl + Ba3(PO4)2 =>
2 K3PO4 + 3 BaCl2 = 6 KCl + Ba3(PO4)2

CH3OH + O2 = CH2O + H2O =>
2 CH3OH + O2 = 2 CH2O + 2 H2O

Na + ZnI2 = NaI + NaZn4 =>
9 Na + 4 ZnI2 = 8 NaI + NaZn4

KHCO3 + H2SO4 = K2SO4 + CO2 + H2O =>
2 KHCO3 + H2SO4 = K2SO4 + 2 CO2 + 2 H2O

NH4OH + HCL = NH4CL + H2O =>
NH4OH + HCL = NH4CL + H2O

Rb2O + H2O = RbOH =>
Rb2O + H2O = 2 RbOH

ZnCl2 + HCl + C4H10O = ZnO + CCl + H2 =>
ZnCl2 + 2 HCl + C4H10O = ZnO + 4 CCl + 6 H2

N2 + H2 = NH3 =>
N2 + 3 H2 = 2 NH3

Al(OH)3 + NaOH = NaAlO2 + H2O =>
Al(OH)3 + NaOH = NaAlO2 + 2 H2O

 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 107 108 109 110 111 112 113 114 115 116 117 118 119 120 121 122 123 124 125 126 127 128 129 130 131 132 133 134 135 136 137 138 139 140 141 142 143 144 145 146 147 148 149 150 151 152 153 154 155 156 157 158 159 160 161 162 163 164 165 166 167 168 169 170 171 172 173 174 175 176 177 178 179 180 181 182 183 184 185 186 187 188 189 190 191 192 193 194 195 196 197 198 199 200 201 202 203 204 205 206 207 208 209 210 211 212 213 214 215 216 217 218 219 220 221 222 223 224 225 226 227 228 229 230 231 232 233 234 235 236 237 238 239 240 241 242 243 244 245 246 247 248 249 250 251 252 253 254 255 256 257 258 259 260 261 262 263 264 265 266 267 268 269 270 271